A GIS-based multi-criteria decision support model for planning municipal solid waste collection points: A case study of cagdas Neighbourhood, cigli District, Izmir, Turkey - (:unkn) unknown (My University, 2022)
This study aims to develop a geographic information system (GIS)-based multi-criteria decision support model to create optimal plans for locating municipal solid waste (MSW) collection points. The model performs a series of consecutive GIS-based spatial analyses to determine alternative plans. Then, it weighs the alternatives considering the social, economic and environmental criteria to determine the optimum solution through analytical hierarchy process. The model was implemented as a case study in cagdas neighbourhood of Izmir, Turkey. A total of 42 locations were determined as the optimum collection points out of 245 possible collection points, which yields 39% reduction in collection points compared to the existing system. Total number of waste bins and average walking distance to waste collection points were calculated as 129 and 33 m, respectively. The municipal authority would spend 48.79 $ day(-1) on fuel for waste collection and transport. In addition, daily air pollutant emissions generated during the operations were estimated as 2.052 g CO, 0.231 g NMVOC, 8.409 g NOx, 0.954 g N2O, 0.260 g NH3, 0.000227 g Pb and 0.0231 g PM 2.5. The results indicated that 14 out of 69 collection points in the existing collection system were not allocated to any waste source geographically. This study presents a unique method for planning MSW collection points on two key aspects: (1) development of a novel method to determine all possible collection point locations using Thiessen polygons and (2) presenting a holistic planning method considering the impacts of the collection system on the waste generators and waste collectors.
Keywords: Tarımsal Bilimler; Çevre Mühendisliği; Mühendislik ve Teknoloji; Agricultural Sciences; Environmental Engineering; Engineering and Technology; MÜHENDİSLİK, ÇEVRE; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ÇEVRE BİLİMLERİ; Çevre / Ekoloji; Tarım ve Çevre Bilimleri (AGE); ENGINEERING, ENVIRONMENTAL; ENGINEERING; Engineering, Computing & Technology (ENG); ENVIRONMENTAL SCIENCES; ENVIRONMENT/ECOLOGY; Agriculture & Environment Sciences (AGE); Aquatic Science; Waste Management and Disposal; General Engineering; Pollution; Environmental Chemistry; Nature and Landscape Conservation; Engineering (miscellaneous); Environmental Science (miscellaneous); Physical Sciences; Life Sciences; Solid waste management; waste collection; waste bin; GIS; voronoi diagram; Thiessen polygons; AHP; GEOGRAPHICAL INFORMATION-SYSTEM; OPTIMIZATION; BINS; METHODOLOGY; TRANSPORTATION; LOCATIONS; DESIGN; NUMBER; CITY